Georgian Borrowings in XVI-XVIII cc. Armenian Sources - POGHOSYAN, NORAYR (Bulletin of Yerevan University B: Philology, 2021)
Throughout centuries the Armenian language has been in direct contact with its southern neighbours , especially with Georgian, pertaining to the caucasian language family. There are a large number of linguistic coincidences between these 2 languages,for example, Armenian “ti”, meaning big, and Georgian “did”, Armenian “sirt” (heart) and Georgian “mkerd”.A number of linguists outline about 50 words that have been passed to Armenian vocabulary from Georgian during the middle ages. These loan-words are mainly concerning craftsmanship, mechanical and administrative sphere. Georgian words have also been found in the Armenian scripts of the 16th to the 18th centuries, e.g. glekhi ( slave), nadjakh( axe), tsil (part, fraction) and so on. As a result of this language intercourse the Armenian language enriched and these borrowed linguistic examples denote cultural and political relations between two nations.